Solar cell split source inverter for induction motor with computer control - Omer N. Mahmmoud; Salam R. Mehdi; Khalaf S. Gaeid; Atheer L. Salih Al-Tameemi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The electrical energy is necessary for daily life, but there is a continuous increase in the usage rate of electric energy. Such an increase is a big problem, which makes us think about using alternative energy for conventional energy, in addition to the problem of pollution resulting from the use of energy generation. Solar energy is a solution for energy in terms of consumption, besides there is no environmental risk in the use of solar energy. In this work, an integrated solar system operating in the daytime has been designed to operate a 3-phase induction motor (IM). The study begins by simulating the system in the MATLAB/Simulink program in order to find out the results and verify them using the same components of the proposed algorithm. The system with photovoltaic (PV) modules 1080 W, whereas the PV array is a direct source of the designed split source inverter (SSI). This SSI is controlled by sine pulse width modulation (SPWM). The maximum power point tracking (MPPT) incremental conductance (INC) method is monitored by a computer connected to the system via a Wi-Fi connection, the 3-phase IM (373) W. The results reveal the efficiency of the system and that it can be versatile.